The effect of short circuit fault on one winding to other windings in FRA - N. F. M. Yasid; M. F. M. Yousof; R. Abd. Rahman; H. Zainuddin; S. A. Ghani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Monitoring and diagnosis of power transformer in power systems have been examined and debated significantly in last few decades. Recently, more researchers have expressed their interest in these issues as the utilities and network operators operating under a rising cost-effecting pressure. Especially, in studying to monitor winding faults which is found to be the most common fault within transformers. This paper addresses the issue of the effect of inter-windings short circuit fault in a Dyn11 connected transformer. The specific aim is to study the effect of fault at winding of other phases to the response of measured phase. Frequency Response Analysis (FRA) which is discovered to be a powerful and sensitive method to examine and evaluate the condition, including the mechanical reliability of the transformer windings is used.